64QAM‐OFDM‐based millimeter‐wave access system using DMT modulation and electrical self‐mixing. Issue 1 (25th November 2013) - Tan, Zefu; Shao, Yufeng; Sun, Yanjing; Wang, Shikui; Luo, Yingxiang
ABSTRACT A novel 60‐GHz optical millimeter‐wave access system with 5 Gb/s 64QAM‐OFDM downlink signals generated by discrete multitone (DMT) modulation, is proposed and experimentally demonstrated. 5Gb/s 64QAM‐OFDM signals are successfully transmitted over 42 km SMF‐28 and a 0.5 m wireless channel. The proposed self‐mixing down‐conversion is adopted in the system, and which can simplify the transmitter and receiver configuration, since it eliminates the need for high‐frequency microwave source at the central station and local oscillator at the base station. The experimental results demonstrate 64QAM‐OFDM downstream signals has higher spectra‐efficiency and lower receiver sensitivity penalty than 16QAM‐OFDM using DMT modulation and electrical self‐mixing. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:259–262, 2014